Analysis of Nursing Care COPD Patients with Pursed Lips Breathing on Reduction Shortness Breath at Arifin Achmad Hospital - Defi Eka Kartika; Sofia Harni; Rosa Desri Meliyanti TB (STIKES Columbia Asia Medan, 2025)
Pursed lips breathing is a method that can be used to breathe effectively and get the amount oxygen needed. The benefits of pursed lips breathing or pursed lips breathing are reducing hyperinflation in the lungs by increasing intra-airway pressure to prevent lung collapse and can also increase the speed of respiratory air flow, and optimize the process. The effect of applying pursed lips breathing on reducing shortness of breath. Application Method: This type of application is a quasi-experiment with a pre test-post test design with a control group. The population in this study was patients with chronic obstructive pulmonary disease who experienced shortness of breath when hospitalized. The sample consisted of one person in the intervention group. The instruments used were questionnaires and flip sheet media. Data was collected using a questionnaire and analyzed using descriptive methods. Patients with chronic obstructive pulmonary disease who experienced shortness of breath after being given the intervention experienced a significant reduction in shortness of breath. Pursed lips breathing is a breathing exercise that can be done independently and has an effective effect on reducing shortness of breath in COPD patients.